Assessment of future climate risk in double cropping systems for Brazil - Souza, Livia Maria Brumatti de (2019)
An agricultural practice that contributes to a high production of these grains is double cropping, widely adopted in the main producing regions: Mato Grosso and MATOPIBA. In this system, soybean is planted in the beginning of the rainy season to ensure that climatic conditions are still favorable to plant maize, in the same area and same agricultural calendar. However, in the next years it is expected a climate change as a consequence of changes in atmospheric composition and deforestation of Amazonia and Cerrado biomes. This would affect the sustainability of double cropping until the middle of century, due to a decrease in precipitation in the beginning of rainy season, which leads to a reduction of soybean productivity. Delaying soybean planting dates increase its productivity, but also causes a delay in maize planting dates, which may lead to losses in maize productivity. The goals of this work are to evaluate climate change effects on second crop maize and the sustainability of double cropping system until 2050, in the main producing regions. The simulations showed a decrease in maize productivity as soybean is planted later. The soybean planting date threshold that ensures an increase in soybean productivity without losses in maize productivity is October 05. Adaptation measures, such as the reduction of phenological cycle of both crops, were tested from the gross revenue for the system in the future, considering that planting dates do not change until 2050. Total cycle lengths of the system of about 220, 200 and 180 days showed that as total cycle duration reduces, the gross revenue of the system increases, being 180 days combination the one that has higher gross revenue in MT. In a scenario with intense deforestation, the suggested adaptation measure does not attenuate the effects of climate change and leads to lower gross revenue values. In MATOPIBA, the reduction in the total phenological cycle of the system does not reduce the climate change effects in any scenario. The analysis of gross revenue showed that even the combination of cultivars with shorter cycle length could not achieve or exceed the reference gross revenue. Other adaptation measures should be adopted together with cultivars adaptation in MT. The climate change effects in MATOPIBA might be stronger and adaptation measures need to be more intense than in MT.